Comparative research of hierarchical CoS2@C and Co3S4@C nanosheet as advanced supercapacitor electrodes. (April 2023) - Wei, Fuxiang; Li, Yingxin; Wang, Hao; Shu, Tie; Yuan, Junzhuo; Lu, Guoge; Lin, Bo; Gao, Zhan; Wang, Qingliang; Qi, Jiqiu; Sui, Yanwei
Abstract: Transition metal sulfides (TMSs) are regarded as promising candidates for supercapacitors owing to their low cost, excellent redox reversibility, and electronic conductivity. However, slow ion diffusion and sharp volume expansion during electrochemistry hinder the application. Herein, the 2D leaf-like ZIF-67 (ZIF-67-L) is used as the precursor for amelioratinge the calcination and then sulfuration process, and the novelly hierarchical structures of CoS2 and Co3 S4 nanoparticles anchored on the carbon skeleton (CoS2 @C and Co3 S4 @C) are constructed. Compared with the inhomogeneous distribution of nanoparticles of Co3 S4 @C, the larger specific surface area is provided by numerous CoS2 @C nanoparticles embedded in the 2D carbon skeleton and connected into sheets through effectively morphological construction, which provides more redox channels and active sites for electrochemical reactions. The CoS2 @C electrode presents a superior electrochemical property with a high specific capacitance of 1151 F g −1 at 1.0 A g −1, which is 1.69 times larger than those of Co3 S4 @C. Density functional theory (DFT) calculations illustrate that CoS2 can transfer much more charge and have higher electronic activity in the process of OH − adsorption as compared with Co3 S4, which proves that CoS2 has better conductivity. Moreover, an asymmetric supercapacitor constructed with the CoS2 @C//reduced graphene oxide (RGO) displays a high energy density of 46.52 Wh kg −1 at a power density of 800 W kg −1 . This work provides theoretical and methodological guidance for the rational composition control and distinct morphological preparation of transition metal sulfides. Highlights: Novel hierarchical CoS2 and Co3 S4 nanosheets grown on carbon cloth are obtained. CoS2 @C exhibits a high supercapacitor performance (1151 F g −1 at 1 A g −1 ). The CoS2 @C//RGO achieves a high energy density and cycling stability. DFT demonstrates that CoS2 has better electrical conductivity than Co3 S4 .